The Influence of Humid Atmosphere during the MAPbI3 Perovskite Layer Preparation on the Characteristics of Its Solar Cells. (August 2019) - Nurunnizar, Adhita Asma; Hidayat, Rahmat
Abstract: Organometal halide perovskite (hybrid perovskite) materials have emerged as a promising material for high power conversion efficiency and low-cost solar cells. The formation of organo-metal halide perovskite layer, however, is very sensitive to some process parameters such as concentration, temperature, and humidity. In this study, we report the preparation of CH3 NH3 PbI3 (MAPbI3 ) perovskite crystal layers under a relatively humid air atmosphere and investigated the characteristics of their solar cells with both mesoporous cell structure and planar cell structure. Due to high humidity, we found that the formed layer tends to form a shiny grey to black color layer on the top of the dark brown color perovskite layer. This layer showed poor x-ray diffraction (XRD) pattern and caused poor solar cell performance. The formation of this layer, however, can be prevented by anti-solvent treatment during the preparation of perovskite layer.